Analysing the elements of 3D design in semi immersive virtual reality digital learning - Mohd Rashdan, Nurain Hayati; Mohamed Ghazali, Nabila Aimi; Che Din, Sharkawi; Mohd Lazim, Nur Aniza (Universiti Teknologi MARA, Perak, 2025)
This study explores the role of 3D design features in semi-immersive virtual reality (VR) and their potential to enhance digital learning experiences. Given the growing integration of VR in education, understanding key design elements—such as space, form, line, plane, texture, colour, and value—is essential for creating immersive and engaging learning environments. Through a qualitative content analysis of four semi-immersive VR teaching videos, this research examines how these elements influence user engagement. The findings highlight that shape, colour, value, and texture each contribute uniquely yet interdependently to the structuring of user experience in semi-immersive VR settings. By offering insights into the strategic application of 3D design principles, this study provides valuable guidance for educators and developers aiming to optimise digital learning environments, thereby advancing the effectiveness of VR-based education.